Is BRCA2 involved in early onset colorectal cancer risk?. Issue 4 (26th December 2019) - Gay‐Bellile, Mathilde; Privat, Maud; Martins, Alexandra; Caputo, Sandrine M.; Pebrel‐Richard, Céline; Cavaillé, Mathias; Viala, Sandrine; Corsini, Carole; Rodrigues, Michael; Barnich, Nicolas; Bidet, Yannick; Uhrhammer, Nancy; et al.
Abstract : A, Closed symbols indicate patients affected with cancer. Open symbols indicate healthy individuals. The type of cancer and age at presentation are given in brackets. Blue circle represents c.4471_4474del variant and red circle represents the c.9648 + 1G > A. B, RNA was extracted from blood of patient III‐3 and his sisters III‐1 and III‐4. RT‐PCR analysis was performed with primers mapping to exons 25 and 27, and PCR products were separated by Bioanalyzer electrophoresis. The sizes of the DNA marker (M) are indicated to the left. LM, lower marker; UM, upper marker. C, Each RT‐PCR product from patient III‐3 was gel‐purified and analyzed by Sanger sequencing. The 297‐bp band corresponds to the reference BRCA2 transcript and the 150‐bp band corresponds to a BRCA2 transcript lacking exon 26.